Consumer perceptions and behaviour towards branded commodities. Issue 1 (11th August 2021) - Singh, Jaywant; Dall'Olmo Riley, Francesca
Abstract: This study investigates consumers' perceived differentiation of branded commodities. Using data from three countries, across four commodity categories, the study examines consumers' brand/attribute associations, brand commitment, and loyalty‐related brand performance measures that are benchmarked against the output from the well‐established NBD‐Dirichlet model. The brand perceptions and brand performance data provide convergent evidence of systematic variations with market share (or brand penetration), rather than idiosyncratic brand differentiation related to the characteristics or equity of individual commodity brands. Overall, the results show that even commodity brands follow the well‐established Dirichlet‐type empirical patterns. The implication is that communication and other marketing‐mix activities should aim to constantly remind consumers of the brand, maintaining the market shares, rather than setting unrealistic targets for increasing loyalty or accentuating brand differentiation.